Design of Ammunition Displacement Stopper of Mortar Automatic Magazine based on Cam Drive - Liu Song; Gao Yuefei; Xin Yibing; Zhu Bowen (Jixie chuandong)
The physical construction and transmission principle of ammunition displacement stopper in a certain automatic howitzer are analyzed,and the similar device applied to mortar automatic magazine is designed based on features of mortar ammunition and chain shell pushing mechanism. The key point of lock-unlock problem is solved by creatively using the motion of shell pushing and the principles of cam drive. The rotation angles and contact forces curve of key parts are obtained from simulation analysis in ADAMS,the results show that the device is feasible and reliable.